2022
DOI: 10.1021/acsami.1c20789
|View full text |Cite
|
Sign up to set email alerts
|

Nonsacrificial Additive for Tuning the Cathode–Electrolyte Interphase of Lithium-Ion Batteries

Abstract: Solid–electrolyte interphases is essential for stable cycling of rechargeable batteries. The traditional approach for interphase design follows the decomposition of additives prior to the host electrolyte, which, as governed by the thermodynamic rule, however, inherently limits the viable additives. Here we report an alternative approach of using a nonsacrificial additive. This is exemplified by the localized high-concentration electrolytes, where the fluoroethylene carbonate (FEC) plays a nonsacrificial role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…It is speculated that the LiFSI salt in LFSI-ether electrolyte shows no significant decomposition but just suffers a breakage of S–N bonds to form SO 2 F and/or N-SO 2 F. This agrees well with our recent work, in which it is found that the S–N bond will break first when the FSI – anion is oxidized and the primary decomposition products of FSI – anion in CEI are SO 2 F (or N-SO 2 F) . This is also consistent with the previous report that, in the FSI – anion structure, the N–S bond is the weakest bond (192.7 kJ mol –1 ), while the F–S bond is much stronger (652.3 kJ mol –1 ), indicating that the FSI – anion could prefer to decompose to form the fragments of SO 2 F and/or N-SO 2 F . The limited LiF species is more likely from the decomposition of TTE or the reaction between TTE and active lithiation product Li 2 S 2 , which will be discussed in following sections.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is speculated that the LiFSI salt in LFSI-ether electrolyte shows no significant decomposition but just suffers a breakage of S–N bonds to form SO 2 F and/or N-SO 2 F. This agrees well with our recent work, in which it is found that the S–N bond will break first when the FSI – anion is oxidized and the primary decomposition products of FSI – anion in CEI are SO 2 F (or N-SO 2 F) . This is also consistent with the previous report that, in the FSI – anion structure, the N–S bond is the weakest bond (192.7 kJ mol –1 ), while the F–S bond is much stronger (652.3 kJ mol –1 ), indicating that the FSI – anion could prefer to decompose to form the fragments of SO 2 F and/or N-SO 2 F . The limited LiF species is more likely from the decomposition of TTE or the reaction between TTE and active lithiation product Li 2 S 2 , which will be discussed in following sections.…”
Section: Resultssupporting
confidence: 92%
“…), indicating that the FSI − anion could prefer to decompose to form the fragments of SO 2 F and/or N-SO 2 F. 38 The limited LiF species is more likely from the decomposition of TTE or the reaction between TTE and active lithiation product Li 2 S 2 , which will be discussed in following sections.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cations are small in size with high positive charge densities, and aprotic polar solvents commonly used in electrolytes possess strong nucleophilic sites (e.g., carbonyl oxygen). Therefore, solvents have the potential to compete with anions for the cation solvation, forming solvation shells in electrolytes (Figure a). This phenomenon has been verified by many experimental characterizations. MD simulations allow a concrete observation of the solvation structures of cations at the microscopic level (Figure b) .…”
Section: Electrolyte Microstructuresmentioning
confidence: 99%
“…A uniform CEI layer about ∼12 nm was found on the surface of the V 2 O 5 electrode in the DSON‐containing electrolyte and the separator showed a clean surface without dark powders on it. Such homogeneous and thin CEI film indicate that the deposited sediments from the electrolyte are not incorporated into the V 2 O 5 interphase, providing effective protection for V 2 O 5 electrode from crystal structure and valid suppression of the electrolyte decomposition [17] . Thus, the SAED image for V 2 O 5 electrode cycled in the DSON‐containing electrolyte shows unambiguous diffraction spots (Figure 2l).…”
Section: Results and Discussmentioning
confidence: 99%